2020
DOI: 10.1038/s41586-020-2639-4
|View full text |Cite|
|
Sign up to set email alerts
|

Phase I/II study of COVID-19 RNA vaccine BNT162b1 in adults

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

68
1,172
13
27

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 1,360 publications
(1,339 citation statements)
references
References 24 publications
(32 reference statements)
68
1,172
13
27
Order By: Relevance
“…Effect of spike mutation D614G on neutralization susceptibility. All of the COVID-19 vaccines currently in clinical trials are based on the original D614 spike sequence 19,20 . An important question is whether substitution D614G could reduce vaccine e cacy, assuming G614 virus continues to circulate.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of spike mutation D614G on neutralization susceptibility. All of the COVID-19 vaccines currently in clinical trials are based on the original D614 spike sequence 19,20 . An important question is whether substitution D614G could reduce vaccine e cacy, assuming G614 virus continues to circulate.…”
Section: Resultsmentioning
confidence: 99%
“…vaccines currently in clinical trials are based on the original D614 spike sequence 19,20 . An important question is whether substitution D614G could reduce vaccine efficacy, assuming G614 virus continues to circulate.…”
Section: Effect Of Spike Mutation D614g On Neutralization Susceptibilmentioning
confidence: 99%
“…Multiple studies employing a variety of vaccine formulations and modalities have now demonstrated that SARS-CoV-2 viral neutralization titers in small animals including mice and guinea pigs are predictive of immunogenicity in macaques and humans ( Figure 5E) [17][18][19][20]22,23,[33][34][35][36][37][40][41][42][43]45 . Despite promising immunogenicity in several cases, all of the above liquid formulations were either refrigerated or frozen prior to use.…”
Section: Discussionmentioning
confidence: 99%
“…Over 150 vaccine candidates are under development globally 16 . Some vaccine candidates that have entered rapidly into clinical phase testing include mRNA vaccine candidates by Moderna (mRNA-1273), BioNTech (BNT162b1) 17 , and CureVac (CVnCoV), a Chimpanzee Adenovirus vector vaccine by University of Oxford and AstraZeneca (ChAdOx1-S) 18 , a non-replicating adenovirus type-5 (Ad5) vaccine by Cansino (Ad5-nCoV) 19 , a DNA vaccine by Inovio (INO-4800) 20 , inactivated virus vaccines by Sinovac (PiCoVacc) 21 and Bharat Biotech (COVAXIN), a native like trimeric subunit spike protein vaccine by Clover Biopharmaceuticals /GSK/Dynavax (SCB-2019), and a full length recombinant glycoprotein nanoparticle vaccine by Novavax (NVX-CoV2373) 16,22 .…”
Section: Introductionmentioning
confidence: 99%